Q: pemdas : 6 x 3 + 10 ÷ 2

A: 6 x 3 + 10 ÷ 2 = 18+5 = 23

Expert answered|AngelInDisguise|Points 2417|

Question|Rated good

Asked 12/10/2011 3:00:11 PM

Updated 2/13/2014 3:15:22 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Confirmed by debnjerry [2/13/2014 3:15:22 PM]

Rating

There are no new answers.

(6x^2 – 25x – 10) ÷ (3x + 2) (show steps)

Question

Not Answered

Updated 5/24/2016 12:47:24 PM

1 Answer/Comment

(6x^2 – 25x – 10) ÷ (3x + 2)

= (6x^2/3x + 2) + (-25x/3x + 2) + (-10/3x + 2)

= 2x - 29/3 R. 28/3

= (6x^2/3x + 2) + (-25x/3x + 2) + (-10/3x + 2)

= 2x - 29/3 R. 28/3

Added 5/24/2016 12:47:24 PM

This answer has been confirmed as correct and helpful.

Solve for X: X2 + 3x – 28 = 0 (show steps)

Question

Not Answered

Updated 8/17/2014 6:24:47 PM

1 Answer/Comment

x^2 + 3x - 28 = 0;

(x + 7)(x - 4) = 0;

x + 7 = 0; x = -7;

x - 4 = 0; x = 4

x = {-7, 4}

(x + 7)(x - 4) = 0;

x + 7 = 0; x = -7;

x - 4 = 0; x = 4

x = {-7, 4}

Added 8/17/2014 6:24:44 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/17/2014 6:30:48 PM]

pemdas: 5 + 2^2 x 3 ÷ (5 - 2)

Question

Not Answered

Updated 7/7/2014 7:20:58 PM

1 Answer/Comment

5 + 2^2 x 3 ÷ (5 - 2)

= 5 + 4 x 3 ÷ (3)

= 5 + 12 ÷ 3

= 5 + 4

= 9

= 5 + 4 x 3 ÷ (3)

= 5 + 12 ÷ 3

= 5 + 4

= 9

Added 7/7/2014 7:20:58 PM

This answer has been confirmed as correct and helpful.

x^2 + 9x+ 14 A. (x + 7)(x - 2)
B .(x + 7)(x + 2)
C. (x + 14)(x + 1)

Question

Not Answered

Updated 7/7/2014 7:23:03 PM

1 Answer/Comment

x^2 + 9x + 14 = (x + 7)(x + 2)

Added 7/7/2014 7:23:03 PM

This answer has been confirmed as correct and helpful.

x^0 is equal to x true or false **Weegy:** x^3 = x*x*x
x^2 = x*x which is x^3 divided by x
x^1 = x which is x^2 divided by x
x^0 = hmm, let's try x^1 divided by x - oh, it's one! Convenient. I hope that was helpful! Thank you for using Weegy! Have a great day! {smile} (More)

Question

Expert Answered

Updated 12/15/2011 4:06:52 PM

1 Answer/Comment

The statement is false. x^0 is always equal to 1. If the exponent is 0, then you get 1.

Added 12/15/2011 4:06:52 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/28/2014 10:36:06 AM]

26,995,894 questions answered

There are no comments.